Behavior of cement concrete confined by fabric-reinforced geopolymer mortar under monotonic and cyclic compression. (December 2021) - Wang, Huailiang; Wu, Yuhui; Qin, Xiaoliang; Li, Lei; Chen, Huihua; Cheng, Baoquan
Abstract: As an eco-friendly inorganic cementitious matrix material, a geopolymer mortar combined with short-cut fibers and fiber meshes represents a novel strengthening system, which has been proven to be effective in strengthening existing concrete structural members. However, the behavior of cement concrete cylinders confined by fabric-reinforced geopolymer mortar (FRGM) under compression is unclear. Therefore, in this work, experimental studies were performed to investigate the effects of the number of strengthening layers, matrix strength of the strengthening system, and loading path on the compressive behavior of basalt–FRGM-confined concrete. The experimental results show that two or three layers of the FRGM jacket can help substantially improve the peak stress and its corresponding axial deformation, ductility, and energy absorption ability. The envelope of the cyclic stress–strain curve is consistent with the monotonic stress–strain curve of an identical group of specimens with the same confinement. The residual plastic strain increases with repeated loading cycles, whereas the new reloading stress deteriorates. Regression models are proposed to predict the peak stress and corresponding axial strain in the basalt-FRGM-confined concrete. Finally, monotonic and hysteretic constitutive models for the FRGM-confined cement concrete are developed and compared with the experimental curves. The experimental results provide new insights into the strengthening properties of geopolymer composites and theoretical support for their application. Notably, geopolymer composites can be used in repairing aging and damaged concrete structures while ensuring a low carbon footprint.